2002
DOI: 10.1124/jpet.301.1.21
|View full text |Cite
|
Sign up to set email alerts
|

The Angiotensin Type 1 Receptor Antagonist, Eprosartan, Attenuates the Progression of Renal Disease in Spontaneously Hypertensive Stroke-Prone Rats with Accelerated Hypertension

Abstract: The effects of the angiotensin type 1 (AT 1 ) receptor antagonist, eprosartan, were studied in a model of severe, chronic hypertension. Treatment of male spontaneously hypertensive stroke prone rats (SHR-SP) fed a high-fat, high-salt diet with eprosartan (60 mg/kg/day i.p.) for 12 weeks resulted in a lowering of blood pressure (250 Ϯ 9 versus 284 Ϯ 8 mm Hg), renal expression of transforming growth factor-␤ mRNA (1.5 Ϯ 0.2 versus 5.4 Ϯ 1.4) and the matrix components: plasminogen activator inhibitor-1 (5.2 Ϯ 1.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Oxidative stress leads to the activation of transcription factors such as nuclear factor kappa B, which in turn activate genes that trigger inflammation, including ICAM-1 [37]. Because fasudil inhibits the generation of reactive oxygen species [10], the inhibition of Rho-kinase might decrease the gene expression of ICAM-1 via the inhibition of ROS. In the present study, high-dose fasudil treatment significantly reduced mRNA expressions of ICAM-1 and p40phox and p47phox in association with the decrease in macrophage/ monocyte infiltration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress leads to the activation of transcription factors such as nuclear factor kappa B, which in turn activate genes that trigger inflammation, including ICAM-1 [37]. Because fasudil inhibits the generation of reactive oxygen species [10], the inhibition of Rho-kinase might decrease the gene expression of ICAM-1 via the inhibition of ROS. In the present study, high-dose fasudil treatment significantly reduced mRNA expressions of ICAM-1 and p40phox and p47phox in association with the decrease in macrophage/ monocyte infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…SHR-SP were used as a model of severe hypertension in this study because of the presence of extensive end-organ damage, including nephrosclerosis [10]. The rats were fed a low-salt diet (0.12% NaCl) during a 2-week acclimatization period.…”
Section: Experimental Animals and Designmentioning
confidence: 99%
“…at ASPET Journals on May 9, 2018 jpet.aspetjournals.org necessary for renal protection by other drugs in the same animal model (Barone et al, 1996;Abrahamsen et al, 2002). Similarly, clinical studies indicated that ARBs improve vascular function independently of the blood pressure-lowering effect (Klingbeil et al, 2002;Lewis, 2002;Viberti et al, 2002).…”
Section: Anti-inflammatory Effects Of Valsartan In Shrsp 993mentioning
confidence: 99%
“…The animals were fed either chow (13% fat, 62% carbohydrate, 25% protein, 3.41 kcal/g) or HFDs (33% fat, 53% carbohydrate, 14% protein, 4.4 kcal/g) for 12 wk, following our previously published methods (31). We and others have previously reported that HFD (30-33% energy from fat) promotes the development of risk factors of metabolic syndrome such as hypertension, renal damage, and stroke in SHRSP rats (31,(51)(52)(53)(54). Because 33% dietary fat more closely resembles the recommended calories from dietary fat for humans (55), this fat concentration was selected for the current study.…”
Section: Methodsmentioning
confidence: 99%